2009
DOI: 10.1099/vir.0.014712-0
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for similarity-assisted recombination and predicted stem-loop structure determinant in potato virus X RNA recombination

Abstract: Virus RNA recombination, one of the main factors for genetic variability and evolution, is thought to be based on different mechanisms. Here, the recently described in vivo potato virus X (PVX) recombination assay . J Virol 83, 7761-7769] was applied to characterize structural parameters of recombination. The assay uses an Agrobacterium-mediated expression system incorporating a PVX green fluorescent protein (GFP)-labelled full-length clone. The clone contains a partial coat protein (CP) deletion that causes d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 72 publications
(64 reference statements)
1
22
0
Order By: Relevance
“…Probing the structure of the SsHV2L 5= UTR by SHAPE indicated that the region contained multiple highly stable stem-and-loop structures, the largest of which contained the putative recombination event with the hypovirus related to VcHV1. Stem-and-loop structures have been shown to be important for similarity-nonessential recombination in RNA viruses (69)(70)(71). Because the 5= UTRs of hypoviruses often are highly structured, it is possible that stem-and-loop structures in this region facilitated the shift of viral replicase from the RNA of one progenitor virus species to the other during virus replication.…”
Section: Discussionmentioning
confidence: 99%
“…Probing the structure of the SsHV2L 5= UTR by SHAPE indicated that the region contained multiple highly stable stem-and-loop structures, the largest of which contained the putative recombination event with the hypovirus related to VcHV1. Stem-and-loop structures have been shown to be important for similarity-nonessential recombination in RNA viruses (69)(70)(71). Because the 5= UTRs of hypoviruses often are highly structured, it is possible that stem-and-loop structures in this region facilitated the shift of viral replicase from the RNA of one progenitor virus species to the other during virus replication.…”
Section: Discussionmentioning
confidence: 99%
“…Co-infections may be rare, especially when the virus strains are ecologically or geographically isolated, or if the immune response limits superinfection (74). Even if co-infection is successful, mechanistic restraints, such as the level of sequence dissimilarity, or the specificity of viral RdRp may prevent the formation of viable hybrids (38,(88)(89)(90)129). Finally, most recombinants are likely to be deleterious and thus purified from the population (103).…”
Section: Recombination and Evolutionmentioning
confidence: 96%
“…During in vitro transcription with purified viral RNA-dependent RNA polymerase (RdRp) and derivatives of viral RNAs, both parental and recombined type products are synthesized. ORFs are marked in green (a,b), noncoding regions are marked with gray lines, and red indicates mutations.Other recombination systems were developed relying on satellite and genomic RNAs of Turnip crinkle virus (TCV)(149), or defective interfering RNAs (DI RNAs) of Tomato bushy stunt virus (TBSV), Cucumber necrosis virus (CNV)(144), and Potato virus X (PVX)(37,38). These systems employed at least two parental RNA molecules with one component carrying a deleterious mutation.…”
mentioning
confidence: 99%
“…RNA structures of the viral genomes can also be an important determinant of viral recombination (49)(50)(51). The detected recombination sites are tightly localized in specific regions of the RNA molecule, as shown for one example in Fig.…”
Section: ϫ8mentioning
confidence: 92%
“…Next, the recombination sites detected in vivo were searched for biases in GC content and sequence similarity because GC content is highly correlated with recombination in higher-order organisms (48), while sequence similarity between the two genomes may favor template switching (49). To test the correlations of GC content and/or sequence similarity within the detected recombination sites in regions D and F, we averaged the two variables over the genome by using a window that extended 10 bp downstream.…”
Section: ϫ8mentioning
confidence: 99%